Do Changes in Emotional States Predict Therapy Alliance in Dutch Male Offenders in Mandated Clinical Care? - Keulen-de Vos, Marije (International journal of offender therapy and comparative criminology, 2022)
Therapy alliance has been studied largely in voluntary psychotherapy but less is known about its predictive factors for positive alliance and treatment outcome in forensic populations. The aim of this study was to examine the relationship between offenders’ emotional states and therapy alliance. Moreover, we were interested in the predictive impact of emotional states early in treatment on alliance at 18 months into treatment. Self-ratings of emotional states and alliance by 103 male offenders, and therapist-ratings for therapy alliance were examined using hierarchical multiple regression analyses. Participants were primarily convicted for violent of sexual offenses, and were diagnosed with antisocial, borderline or narcissistic personality disorders. Healthy emotional states were predictive of mid-treatment agreement on therapy goals and therapist ratings on tasks within the therapy. Unhealthy emotional states were predictive of patient-rated agreement on tasks. Emotional states were not predictive for the reported therapist/patient bond or global alliance ratings. This study emphasizes the importance of healthy emotional states in treatment of offenders with personality disorders.